2019
DOI: 10.1101/789362
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The early life microbiota protects neonatal mice from pathological small intestinal epithelial cell shedding

Abstract: AbstractThe gut microbiota plays a crucial role in regulating and maintaining the epithelial barrier, particularly during early life. Notably, patients with chronic intestinal inflammation have a dysregulated process of renewal and replenishment of the intestinal epithelial cell (IEC) barrier, which is linked to disturbances in the gut microbiota. To date, there are no studies focussed on understanding the impact of inflammatory cell shedding events during the early life develo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…It has been well established that the microbiomes of humans and animals change significantly in early life phases, e.g. after the weaning transition from milk to solid foods (12,16,17), but the longitudinal changes of the gut microbiome throughout adulthood are less well characterized. In this study, we characterized the gut microbiome of conventionally raised adult male C57BL/6J mice at regular fine-scale intervals for two years, which corresponds to the approximate lifespan of this species (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well established that the microbiomes of humans and animals change significantly in early life phases, e.g. after the weaning transition from milk to solid foods (12,16,17), but the longitudinal changes of the gut microbiome throughout adulthood are less well characterized. In this study, we characterized the gut microbiome of conventionally raised adult male C57BL/6J mice at regular fine-scale intervals for two years, which corresponds to the approximate lifespan of this species (10).…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal studies are rarely performed compared to cross-sectional studies, partly due to the convenience of obtaining mice of different ages and accumulative cost of mice maintenance. Cross-sectional studies of the murine gut microbiome are generally focused on the early or later years of the murine life (2,12,13). One such study examined the gut microbiomes of 'young' (24 weeks old), 'middle age' (84 weeks old) (which was not certified by peer review) is the author/funder.…”
Section: Introductionmentioning
confidence: 99%
“…However, we did not observe associated global transcriptional inflammatory immune changes that would be expected if this was the case, but rather global changes in barrier function transcripts and pathways. Furthermore, Bifidobacterium has previously been isolated from C57BL/6 mice (including from our mouse colony), and therefore appears to be a resident rodent gut microbiota member, although it is found at varying abundances in different animal units and suppliers ( Grimm et al., 2015 ; Hughes et al., 2020 ). Indeed, one particular study has shown that high levels of resident Bifidobacterium in mice directly correlated with improved immune responses to cancer immunotherapies ( Sivan et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Colony forming units were counted using a click counter. In SPF animals housed in the same animal facility we have previously shown that Bifidobacterium represents ∼1% of the total gut microbiota [19].…”
Section: Methodsmentioning
confidence: 99%